Review of environmental impacts and applications of biotechnology in the pulp and paper industry in Canada. - Nguyen, Quang A. (University of Ottawa (Canada), 1991)
This thesis examines the environmental issues facing the Canadian pulp and paper industry and the potential application of biotechnology to solve some of these problems and contribute to a sustainable growth in the future. Biotechnology can offer a wide scope of applications including: (1) Plant biotechnology: silvicluture, reforestation, replacement of chemical pesticides with biological control agents. (2) Biopulping and biobleaching: reduce the amount of polluting chemicals used in the production of pulp. (3) Effluent treatment: micro-organisms can be selected to treat mill effluent more effectively. (4) By-product conversion: wood waste can be hydrolyzed by enzyme to sugar, then fermented to ethanol that can be used as a renewable transportation fuel. One of the federal government's objective outlined in the Green Plan is to stabilize the total carbon dioxide emission in Canada. The substitution of gasoline by biomass ethanol would contribute significantly to this goal. (Abstract shortened by UMI.)
Keywords: Business Administration, General.